Experimental study on the drag forces on a twin-tube submerged floating tunnel segment model in current. (November 2020) - Deng, Shi; Ren, Haojie; Xu, Yuwang; Fu, Shixiao; Moan, Torgeir; Gao, Zhen
Highlights: Mean drag force of a twin-tube submerged floating tunnel segment was studied by towing test and self-excited oscillation test. The drag forces of the up- and downstream cylinders act in opposing directions when λ = 2, 3 in the towing test. Vortex induced vibration strongly amplify the drag forces on both cylinders. The VIV response amplitude and the drag force decrease a lot with the decreasing of the submergence. Abstract: In this paper, the drag forces on a rigid segment of a twin-tube submerged floating tunnel (SFT) under various Re number and submergence are experimentally investigated with a simplified rigidly connected tandem twin-cylinder model towed in a tank. The effects of the spacing distance between two cylinders and vortex-induced vibration (VIV) on the drag forces are investigated through stationary and self-oscillation towing tests. It is found that, in the stationary cases, the drag forces on the cylinders act in opposing directions when the spacing ratio is 2 and 3, which leads them attracting each other. Under VIV conditions, the drag forces are significantly amplified. The maximum mean drag coefficients of the up- and downstream cylinders increase from 1.27 to 4.1 and 0.43 to 1.7, respectively. As for the submergence effect, it is found that both the VIV response amplitude and mean drag coefficient decrease with the decreasing of the submerged depth, especially when the depth ratio is below 3.7.